Catholic Workers Associations and “Political Citizenship”. Córdoba in the early 20th Century (Quinto Sol, 2013)
This paper examines the participation of the members of three catholicworkers association -Círculo de Obreros de Córdoba, Asociación Artesanosde San José and Sociedad Católica Popular Italiana- to choose theirauthorities in Córdoba, Argentina during the first decades of the 20thCentury. The study allows us to know that, besides, the indirect electoralsystem applied in the three cases, there are important differences which contributed in different ways to the appropriation of the concept and practice of political citizenship inaugurated in 1912. A diversity of electoral procedures can be found: from a very restricted political position more interested in religion and catholic rituals to one which granted all members the right to choose and be chosen. In the same way, the more “democratic” associations corresponded, as could be expected, to those where internal debate was more regular.
Keywords: voluntary associations; workers; Catholicism; political citizenship